A Case of Small-intestine Perforation Due to Dialysis-Related Amyloidosis - Narita, Michihiko; Takagi, Kenji; Itoh, Akira; Yamaguchi, Naoya; Yamauchi, Kohei; Kanamori, Atsushi; Shiomi, Masaya; Itatsu, Keita; Sekoguchi, Ei (Nippon Shokaki Geka Gakkai zasshi, 2011)
We report a case of rare intestinal perforation due to dialysis-related amyloidosis. A 79-year-old woman undergoing hemodialysis for 17 years, undergoing two operations for right carpal tunnel syndrome, sigmoid colon resection due to diverticulosis bleeding, and medical therapy for angina pectoris, acute heart failure, and pulmonary tuberculosis was admitted and underwent surgery for nontraumatic right femoral neck fracture. Following postoperative abdominal pain and diarrhea, she suffered severe abdominal pain 2 days after surgery. Abdominal computed tomography (CT) showed free air and ascites. Emergency laparotomy confirmed two small-intestine perforation sites necessitating partial resection and anastomosis. Histopathologically, amyloid deposits were found perivascularly in the submucosal layer around perforations. Postoperative wound infection, deep-seated mycosis, severe diarrhea, and acute heart failure developed at the time all healed in conservative treatment, and the woman was discharged 78 days after emergency surgery.